A questionnaire-based comparative study of postoperative quality of life between laryngotracheal separation and tracheoesophageal diversion. Issue 2 (April 2018) - Ishimaru, Tetsuya; Sugiyama, Masahiko; Arai, Mari; Satoh, Kaori; Uotani, Chizue; Takahashi, Masataka; Takami, Shohei; Katoh, Reiko; Goshima, Tsubasa; Fujishiro, Jun
Abstract : Purpose: Whether tracheoesophageal diversion (TED) is preferable to laryngotracheal separation (LTS) is unclear. This study examined the need for tracheoesophageal anastomosis by reviewing complications after TED and LTS and administering a questionnaire on postoperative quality of life. Patients and methods: Medical records of TED/LTS cases performed at a single institution from 2003 to 2015 were retrospectively reviewed and a questionnaire was administered to parents of patients at an outpatient visit. Results: A total of 40 TED and 18 LTS cases were included. Complications occurred in six TED cases and one LTS case, with no significant differences between groups ( P =0.42). A total of 22 parents of patients (TED 16 cases; LTS six cases) completed the questionnaire. Voice production was reported in three TED cases and two LTS cases. Patients indicated that suctions were 'decreased' in 13 and 'unchanged' in two TED cases, but 'decreased' in one and 'unchanged' in five LTS cases ( P =0.0055). Readmissions were 'increased' in one and 'decreased' in 14 TED cases, but 'decreased' in three and 'unchanged' in three LTS cases ( P =0.015). Conclusion: Postoperative complication rate was equivalent between groups, and the numbers of suctions and readmissions were decreased in the TED group. Therefore, tracheoesophageal anastomosis should be performed more commonly.